Heat transfer characteristics of flat plate heat pipe with closed meandering channel composed of sintered metal porous sidewalls - Natsuki KIMURA; Takuya ISE; Kizuku KUROSE; Kazushi MIYATA (Journal of Thermal Science and Technology)
Pulsating heat pipes (PHPs) are valuable for compact cooling applications. This study introduces a novel heat pipe design: a flat-plate heat pipe with a closed meandering channel and sintered metal porous sidewalls (porous HP). The effects of initial liquid volume fraction and inclination angle on heat transfer characteristics and flow behavior were examined and compared with those of a conventional PHP. The porous HP contains a rectangular meandering channel, 1.0 mm wide and 0.8 mm deep, with 20 turns. Its sintered metal porous structure, made from fine copper powder, has a tree-like morphology and 0.65 porosity. FC-72 served as the working fluid. At an inclination angle of 0°, boiling did not occur; however, thermal resistance was lower with liquid filling than without, indicating heat transfer through evaporation and capillary-driven recirculation. In the bottom-heated condition with an inclination angle greater than 0°, boiling and self-excited oscillations emerged despite the side walls being composed of porous material, significantly reducing thermal resistance. The lowest thermal resistance was recorded at a liquid fraction of 0.7 and an inclination angle of 90°. Flow oscillations in the meandering channel and liquid wetting within the porous medium enhanced heat transfer. The porous HP achieved a lower minimum thermal resistance and higher maximum effective thermal conductivity than conventional PHP.